Hazardous Air Pollutants and Adverse Birth Outcomes in Portland, OR - Willis, Mary (Environ Epidemiol, 2019)
The impact of multiple hazardous air pollutant (HAP) exposures during pregnancy on adverse birth outcomes is unknown. We examined associations between cumulative and individual HAP exposures and adverse birth outcomes in Portland, OR, a region that has exceeded HAP air quality guidelines for decades. METHODS: We used vital statistics records in the Portland Metropolitan Region from 2000 to 2014 (n = 279,051 births). Prenatal exposure to 19 HAPs was assessed using a dispersion model applied to maternal residential address at delivery. We used linear and logistic multivariate regression models to assess associations between individual and cumulative HAP exposures and preterm term (PTB), term birth weight (TBW), and small for gestational age (SGA), adjusting for several potential individual and neighborhood confounding factors. RESULTS: We observed no associations for composite HAP exposure metrics and adverse birth outcomes. Associations were observed in fully adjusted models comparing the highest to lowest quintiles of exposure for certain HAPs including chromium VI and TBW (−12.70; 95% confidence interval [CI]: −23.10, −2.31); 1,3-butadiene and TBW (−16.86; 95% CI: −29.66, −4.06) and SGA (1.18; 95% CI: 1.07, 1.30); and cadmium and TBW (−31.37; 95% CI: −56.20, −.54). For some HAP metrics, we observed higher HAP exposures for minority groups and large unadjusted associations between other HAPs and adverse birth outcomes, but most associations were attenuated in adjusted models. CONCLUSIONS: Adverse birth outcomes were not consistently associated with most HAP exposures in Portland, OR, although some specific air toxic exposures warrant further attention.